Portal vein thrombosis in patients with liver cirrhosis - Savić Željka; Damjanov Dimitrije; Latinović-Bošnjak Olgica; Janjić Nebojša; Dejanović Božidar; Krnetić Žarko; Vračarić Vladimir (Vojnosanitetski Pregled)
Background/Aim. Portal vein thrombosis (PVT) in patients with liver cirrhosis (LC) has a prevalence of 0.6–26%. It is most commonly discovered incidentally as part of the evaluation of LC or in the context of acute decompensation of LC due to portal hypertension. The aim of the study was to determine the prevalence of PVT in patients with LC in relation to the severity of the disease and individual elements of portal hypertension. Methods. A total of 326 patients treated for LC decompensation were included in a retrospective study. Standard laboratory analyses, abdominal ultrasonography and/or computed tomography, and esophagogastroduodenoscopy were performed. Results. The diameter of the portal vein (PV) differed between patients without esophageal varices (12.2 mm) and those with large varices (13.6 mm), p = 0.026. PVT was identified in 6.1% of patients with LC. The patients were classified according to the Child-Pugh scoring system, which has the A, B, and C categories used to assess the severity of liver disease. PVT was present in 3.0% of patients in class C and 12.0% in class B, while none of the patients in class A had PVT (p = 0.005). PVT was present in 4.4% of patients with small varices and 16.7% with large varices (p < 0.001). There was no difference in the presence of PVT between the groups of patients with and without variceal bleeding nor between groups with different degrees of ascites. A fatal outcome occurred in 29.4% of patients, but there was no difference between patients with and without PVT. Conclusion. PVT is present in more advanced stages of LC and predominantly in patients with large esophageal varices. There was no higher prevalence of PVT observed with the occurrence of variceal bleeding or with the death outcome in patients with LC.